Replicating the pathways to resilience: demographic predictors, self-efficacy, and inclusive teaching among pre-service teachers - Shuakbayeva, Zhulduz; Ospanova, Bibigul; Kalkeyeva, Kamariyash; Orazaliyeva, Rsaldy; Nurekenova, Aigul (Frontiers in Education, 2025)
BackgroundWhile the interplay between teacher self-efficacy and resilience is established, this study probes the nuanced influence of specific demographic factors – gender, teaching experience, and familial ties to teaching – on this dynamic within inclusive education contexts. Existing research presents equivocal evidence regarding gender’s role and sparse insight into the impact of familial connections to teaching on these constructs. This investigation replicates and extends prior inquiry by Yada et al. (2021) in a distinct socio-cultural setting, utilizing a larger cohort of pre-service teachers (n = 283 vs. 150 in the original study) and incorporating qualitative insights to enrich quantitative finding. This replication is crucial as it examines how demographic predictors, which have shown context-dependent effects in prior research, operate within a system characterized by differing teacher education pathways and social perceptions of the profession.MethodsA mixed-methods design was employed, combining quantitative survey data (demographics, self-efficacy, resilience scales) with qualitative interviews. Quantitative data analysis used structural equation modeling and mediation analysis. Inductive thematic analysis was applied to the qualitative data gathered from interviews.ResultsTeaching experience strongly and significantly predicted both inclusive self-efficacy and resilience, with self-efficacy also mediating the experience-resilience link. In a key divergence from prior research, familial ties to teaching showed a negligible impact on self-efficacy and a marginal, non-significant influence on resilience. Moreover, gender did not differentiate self-efficacy or resilience, contrasting with previous findings that observed gender-based differences. Qualitative data revealed a multifaceted picture of challenges, coping strategies, and training needs. Diverse conceptualizations of inclusion emerged alongside variable confidence levels in implementing inclusive practices. Self-efficacy was domain-specific and heavily influenced by mastery experiences. Barriers included time constraints and personal limitations, while support networks and mentorship enhanced both self-efficacy and resilience.ConclusionThe findings underscore a learning trajectory driven by experiential learning, practical challenges, and emotional processes. Addressing identified barriers and leveraging support networks are crucial for fostering effective inclusive education practices. The study’s replication in a new context highlights that the influence of demographic factors on teacher development is not universal and is instead shaped by the specific national education system and socio-cultural environment.